Application of Low level Lasers in Dentistry (Endodontic) - Asnaashari, Mohammad (J Lasers Med Sci, 2013)
Low level lasers, cold or soft lasers: These lasers do not produce thermal effects on tissues and induce photoreactions in cells through light stimulation which is called photobiostimulation. Power of these lasers is usually under 250mW. The main point differentiating low level lasers and high power ones is the activation of photochemical reactions without heat formation. The most important factor to achieve this light characteristic in lasers is not their power, but their power density for each surfa ceunit (i.e cm(2)). Density lower than 670mW/cm(2), can induce the stimulatory effects of low level lasers without thermal effects. Low level lasers (therapeutic) used today as treatment adjunctive devices in medicine and dentistry. Numerous studies have been performed on the applications of low level lasers in patient pain reduction. Mechanisms of pain reduction with therapeutic lasers and their application are expressed, and the studies realized in this field are presented.